PHONEMIZATION PATTERNS IN THE TOMBATU LANGUAGE OF SOUTHEAST MINAHASA: A SYSTEMATIC REVIEW - Liuw, Jola; Gosal, Nicolas; Lasut, Conny R. (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This research aims to examine systematic sound changes that influence certain sound patterns and classes, through segmentation of language sounds, grouping patterns and sound classes of the Tombatu language. Moreover, this paper also focuses on analyzing the phonological process, explaining variations in speech sounds, describing the process of changes in language sounds, and compiling standard phonetic formulas. The techniques for providing data were tapping techniques, skillful listening techniques, recording techniques, note-taking techniques and using the Tombatu Language Vocabulary instrument based on the Swadesh list (200 Vocabulary). In terms of data analysis, several techniques are conducted according to Larry Hyman's phoneme concept, minimal pairs (1975), and by grouping distinctive characteristics by Chomsky and Halle in Yusuf (1998), Jakobson and Trubetzkoy in Kenstowicz (2007). The results showed that Tombatu language there are no phonemes /f/, /v/, /q/, /z/,/x/ and on the contrary there are other phonemes which are characteristic of the Tombatu language, but do not differentiate the meaning, such as phonemes , /Å¡/, /Ä‘/, /É«/ and there are diphthong phonemes. There are 19 consonant phonemes, 6 vowel phonemes, 9 diphthong phonemes /É›i/,/ai/,/oi/,/ui/ and /aw/,/,(iw/,/uw/,/ew/,/ ow/). Distinctive characteristics of BT phonemes, especially typical BT phonemes. /ÅŸ/ languid, fricative, voiced, alveolar lamino, /Ä‘/ suddenly loose, stop burst, voiced, apico prepalatal, /Å‚/ wide languid, lateral, voiced apico prepalatal, /Å§/ tight loose suddenly, inhibited eruption, sound, apico prepalatal.